The Influence of Family Environment and Peers on Student Learning Discipline at Vocational High School 12 Jakarta: Pengaruh Lingkungan Keluarga dan Teman Sebaya terhadap Kedisiplinan Belajar Siswa di SMK Negeri 12 Jakarta - Putri, Falya Utami; Kartikowati, RR. Sri; Fidhyallah, Nadya Fadilah (Politeknik Assalaam Surakarta, 2025)
Learning discipline in the context of education refers to students' desire and attitude toward the learning process as well as their capacity to adhere to regulations and study plans. Learning discipline entails following guidelines, maintaining regular study schedules, and being able to turn in assignments on time. Furthermore, it is intimately linked to students' dedication to the learning process, personal motivation, and time management. Investigating the degree to which the peer and family environments affect students' learning discipline at SMK Negeri 12 Jakarta is the aim of this study. 103 students made up the sample size for this quantitative study, which was then re-proportioned. Proportional random sampling, a probability sampling approach, was used to choose the respondents. Multiple linear regression analysis was used to examine the study's data. With a significance value of 0.000, which is less than 0.05, the results demonstrated that peers and the home environment both significantly affect learning discipline at the same time. Furthermore, the two factors account for 58.5% of the construction of student learning discipline, according to the study of the coefficient of determination (R²). As a result, it's critical to establish an environment that promotes learning in both the home and the classroom. This includes creating a cozy study space, reducing outside distractions, and promoting candid dialogue between educators, parents, and students.